Fluorescent Hydrogel Producing ZnO for Colorimetric Detection of Glutathione and Cysteine. Issue 20 (21st September 2021) - Kang, Beibei; Tang, Huicheng; Gao, Min; Sun, Tianqi; Zhao, Zengdian; Song, Shasha
Abstract: Supramolecular hydrogels, based on non‐covalent interaction, have outstanding properties, but it is still a big challenge to design hydrogels with higher mechanical properties. In this study, hydrogels with adjustable mechanical properties are prepared by mixing 4′‐(4‐ n ‐butylimidazole)‐ p ‐benzyl‐2, 2′:6′2″‐terpyridine (C4 ‐Ter) and zinc ions (Zn 2+ ) in water. The hydrogels are composed of fibrous structure and hierarchical porous structure, which depends on Zn 2+ concentration. Rheological results demonstrate that the hydrogels exhibit prominent mechanical strength with the elastic modulus ( G ″) and yield stress (τ*) of 200 000 and 1000 Pa, respectively. X‐ray diffraction and Fourier‐transform infrared spectroscopy measurements reveal that the hydrogels are mainly driven by the π–π stacking, metal coordination and hydrophobic effects, hydrogen bonding, etc. ZnO is produced by using C4 ‐Ter/Zn 2+ hydrogel as the precursor. Due to the higher peroxidase activity, the obtained ZnO can be used for colorimetric detection of glutathione (GSH) and cysteine (Cys) with the lower limit detection of 0.7818 and 1.2088 µmol L −1, respectively. Moreover, the ZnO + 3, 3″, 5, 5′‐tetramethylbenzidine (TMB) + H2 O2 sensing system shows higher selectivity for GSH and Cys detection. Therefore, a convenient method to prepare ZnO is developed, which should be an environmentally friendly candidate material in the biomedicine and food industry. Abstract : ZnO as a biosensor realizes the advantageous quality in facial and rapid detection of GSH and Cys by naked eyes.